Gamified AR Narratives and Spatial Experience in Urban Heritage Architecture - Xiao, Lin; Fan, Li; Mokhtar, Noor Aisyah; Mat Sulaiman, Mohd Khairul Azhar (Departemen Arsitektur Fakultas Teknik Universitas Brawijaya, Indonesia, 2026)
The growing adoption of augmented reality (AR) in heritage tourism has created new opportunities for visitor interpretation and engagement. However, most AR applications remain content-oriented and pay limited attention to the spatial characteristics of heritage environments. This study examines how spatially embedded gamified AR narratives influence spatial experience and architectural interpretation in urban heritage settings. A sequential mixed-methods approach was conducted at three heritage sites in Chengdu, China, representing linear, axial, and dispersed spatial typologies. Data were collected through pre- and post-AR surveys with 372 participants, semi-structured interviews with 48 respondents, behavioural observations, and Structural Equation Modelling (SEM). The results show that spatial narrative coherence—the alignment between AR task logic and spatial syntax—is the strongest predictor of spatial immersion (β = 0.59) and indirectly enhances architectural interpretation (β = 0.32). These effects are moderated by visitor typology, with explorers and gamers benefiting most. The findings demonstrate the importance of space-centred AR design and propose a spatially adaptive framework that aligns narrative structures with heritage environments, offering practical guidance for architects, heritage managers, and AR developers.